A General Evaluation of the Cellular Role in Drug Release: A Clinical Review Study - Karami, Mohammad Hossein; Abdouss, Majid (Clinical Journal of Obstetrics and Gynecology, 2024)
Cells have emerged as highly promising vehicles for delivering drugs due to their unique advantages. They have the ability to bypass immune recognition, navigate biological barriers, and reach difficult-to-access tissues through sensing and active movement. Over the past couple of decades, extensive research has been conducted to understand how cell carriers can overcome biological barriers and influence drug effectiveness. This has resulted in the development of engineered cells for targeted drug delivery to specific tissues. Despite the presence of exciting developments, a comprehensive understanding of the challenges and potential strategies is necessary for the effective clinical application of cell-based drug carriers. This review provides an overview of recent progress and novel concepts in cell-based drug carriers, as well as their potential for translation into clinical practice. Additionally, we delve into important factors and emerging strategies for designing the next generation of cell-based delivery technologies, with a particular emphasis on achieving greater accuracy and targeted drug administration.